Komunikasi Matematik bagi Siswa di Sekolah Menengah Atas - Faizatul Mustajazah; Rita Sari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
Mathematical communication is a combination of understanding and doingmathematics. The purpose of this research is to review students' mathematicalcommunication skills as measured through tests. The research method used was asurvey method. The research sample taken as a whole or referred to as total sampling.Data collection tool used in the form of a descriptive test analyzed descriptively. Theresults of the data analysis showed that the mathematical representation ability ofstudents included in the category of adequate or sufficient or equal to 59.70%, in thecategory of less than 40.29%